Antimicrobial Activities of European Propolis Collected from Various Geographic Origins Alone and in Combination with Antibiotics - Al-Ani, Issam Jumaa Nasser; Zimmermann, Stefan; Reichling, Jürgen; Wink, Michael (Medicines, 2018)
Background: Propolis consists of a complex mixture of resinous substances collected by honeybees from different plant sources. The objective of this study was to investigate the chemical composition, biological activities, and synergistic properties with antibiotics of propolis samples collected from various geographic origins (Germany, Ireland, and Czech Republic). Methods: The chemical composition of the propolis was analyzed by Gas Liquid Chromatography-Mass Spectrometry (GLC-MS) and High-performance liquid chromatography (HPLC). The minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) were evaluated by the standard broth microdilution method, while synergistic interactions were assessed by checkerboard dilution and time-kill curve assays. Results: HPLC and GLC-MS analyses revealed that ethanol extract of propolis (EEP) and water extracts of propolis (WEP) contained more than 100 different phytochemicals. The most abundant compounds were aromatic alcohols, aromatic acids, cinnamic acid and its esters, fatty acids, and flavanone (chrysin). Czech propolis showed the highest phenolic content (129.83 ± 5.9 mg CAE/g) followed by Irish propolis and German propolis. Furthermore, Irish propolis exhibited the highest value of total flavonoid content (2.86 ± 0.2 mg QE/g) and antioxidant activity (IC50 = 26.45 µg/mL). All propolis samples showed moderate antibacterial effect against Gram-positive microorganisms with MIC ranging from 0.08 mg/mL to 2.5 mg/mL. Moreover, EEP exhibited moderate activity against Gram-negative bacteria with MIC between 0.6 mg/mL to 5 mg/mL. In addition, EEP displayed moderate antifungal activity (MIC values between 0.6-2.5 mg/mL). The results obtained from time kill-kinetic assay and checkerboard dilution test of two-drug combinations between EEP and antibiotics such as vancomycin, oxacillin, and levofloxacin indicate mainly synergistic interactions against drug-resistant microbial pathogens including MRSA and VRE. Conclusions: The propolis extract synergistically enhanced the efficacy of antibiotics, especially those acting on cell wall synthesis (vancomycin and oxacillin) against drug-resistant microorganisms.
Gesehen am 16.02.2018